2000
DOI: 10.1023/a:1006398401352
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of hepatic metastases from breast cancer

Abstract: We have performed a retrospective study to evaluate whether surgical treatment is beneficial in patients with hepatic metastases from breast cancer. Between September 1985 and September 1998, 25 patients with hepatic metastases (14 solitary and 11 multiple), eight of whom had extrahepatic metastases, underwent hepatectomy. All of the detectable liver metastasis were resected in all of the cases. There were no severe postoperative complications. All but one of the patients received adjunctive polychemotherapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 11 publications
3
52
1
8
Order By: Relevance
“…Presence of EHD had a negative effect in the studies by Sakamoto and Thelen [27,35], but was not significant in other studies [20,21,31].…”
Section: Studies Of Liver Resection (N=25)mentioning
confidence: 66%
See 1 more Smart Citation
“…Presence of EHD had a negative effect in the studies by Sakamoto and Thelen [27,35], but was not significant in other studies [20,21,31].…”
Section: Studies Of Liver Resection (N=25)mentioning
confidence: 66%
“…Interval between primary BC and BCLM was a positive factor in the studies by Selzner, Pocard, and Caralt [20,22,37] but not so in several other studies [21,24,26,27,31,35,36]. Size, site or number of BCLM were not generally found to be of significance, except that >1 BCLM was a negative factor in one study [23] (table 2).…”
Section: Studies Of Liver Resection (N=25)mentioning
confidence: 90%
“…12,13 Following hepatic resection for metastatic breast cancer, 3-year survival rates of 49-53% 5,6,14 and 5-year survival rates of 18-34% have been reported. 4,14,15 However, recurrent disease is commonly seen in these patients, being detected in all of those followed for >1y ear in one study 5 and 63% of survivors at 3 years in another. 6 Although there appears to be a survival benefit for those undergoing hepatectomy, the numbers included in the studies tend to be small, ranging from 15-54; due to the highly selective nature of the treatment group, a control group is never included.…”
Section: Discussionmentioning
confidence: 96%
“…A small group of patients with metastasis confined to the liver (5-12%) 1 appear 2 to have an improved prognosis following hepatic resection and 3-year survival rates of 35-71% have been reported although disease-free survival rates are considerably lower. [3][4][5][6] It has been suggested that hepatic resection improves survival by means of reducing the tumour burden of the patient, thus allowing subsequent hormonal or chemotherapy to be more effective. 7,8 Radiofrequency ablation (RFA) is a relatively simple percutaneous technique that has been demonstrated to be an effective cytoreductive strategy for a variety of metastatic liver malignancies, with few side effects and little disruption of the patients life.…”
mentioning
confidence: 99%
“…14), lung carcinoma (15,16), and breast carcinoma (17 -24). A model of metastasis to the choroid of the eye was reported in which tumor cells also invaded the brain (25).…”
Section: Experimental Model Systems Of Brain Metastasismentioning
confidence: 99%